2013
DOI: 10.1002/rcm.6550
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the ionization probability during desorption/ionization of oligopeptides induced by neutral cluster impact

Abstract: The ion-to-neutral ratio in desorption/ionization of oligopeptides induced by neutral cluster impact was determined to be of the order of 10(-3) to 10(-2). The soft and matrix-free nature of the method in combination with this value of η might be interesting for applications in bioanalytics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Although we have shown that the ionization probability of a given analyte molecule is not strongly influenced by the presence of co-adsorbates or co-constituents in mixed samples 17,24 , the ionization probability may vary from substance to substance 13 . Thus, it is even more important to work under clean conditions as contaminants, depending on their ionization probability, may contribute to the signal much stronger than the analyte.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Although we have shown that the ionization probability of a given analyte molecule is not strongly influenced by the presence of co-adsorbates or co-constituents in mixed samples 17,24 , the ionization probability may vary from substance to substance 13 . Thus, it is even more important to work under clean conditions as contaminants, depending on their ionization probability, may contribute to the signal much stronger than the analyte.…”
mentioning
confidence: 78%
“…. The latter can act as an efficient proton source which further promotes the ionization process in case of ionization via proton uptake (positive ion mode) 13,18 .…”
mentioning
confidence: 99%
“…Thus, the proposed formation of H 2 SO 3 from SO 2 in the cluster and H 2 O in the film seems to be plausible and the resulting increase in H 3 O + concentration might explain the predominance of the cations as well as the observed ionization efficiency. [9,11] Further experiments are necessary to clarify the desorption/ionization mechanism in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In contrast to the techniques using charged (non-reactive) primary particles, we have recently shown that a beam of neutral SO 2 clusters can also be employed for very soft and matrix-free desorption and ionization of oligopeptides. [9][10][11] With the high dipole moment of the SO 2 molecules (1.6 debye), the impacting SO 2 clusters do not only provide the energy necessary for the desorption, but also serve as a transient matrix in which the desorbing molecule is dissolved during the desorption process; as a consequence desorption takes place at comparably low cluster energies (<1 eV/molecule). Shattering of the cluster during and after surface impact then leads to a rapid redistribution of the system's energy thus avoiding heating and fragmentation of the desorbing molecules.…”
mentioning
confidence: 99%
“…27 This is approximately 2 orders of magnitude greater than our numbers when our UY values are corrected for an estimated 10% overall efficiency of transmission and detection in our instrument. It would be good to determine useful yield values for massresolved ion species in the Gebhardt approach.…”
Section: Analytical Chemistrymentioning
confidence: 93%